যদি \(\cfrac{x^2-yz}{a}=\cfrac{y^2-zx}{b}=\cfrac{z^2-xy}{c}\) হয়, তবে প্রমান করো যে \((a+b+c)(x+y+z)\) \(=ax+by+cz\) Madhyamik 2006


\(\cfrac{x^2-yz}{a}=\cfrac{y^2-zx}{b}=\cfrac{z^2-xy}{c}\)
\(=\cfrac{x^2-yz+y^2-zx+z^2-xy}{a+b+c}-----(i)\)

[সংযোজন প্রক্রিয়া করে পাই]



আবার, \(\cfrac{x^2-yz}{a}=\cfrac{y^2-zx}{b}=\cfrac{z^2-xy}{c}\)
বা, \(\cfrac{x^3-xyz}{ax}=\cfrac{y^3-xyz}{by}=\cfrac{z^3-xyz}{cz}\)
\(=\cfrac{x^3-xyz+y^3-xyz+z^3-xyz}{ax+by+cz}\)
\(=\cfrac{x^3+y^3+z^3-3xyz}{ax+by+cz}-----(ii)\)

[সংযোজন প্রক্রিয়া করে পাই]




\((i)\) ও \((ii)\) নং সমীকরন থেকে পাই,
\(\cfrac{x^2-yz+y^2-zx+z^2-xy}{a+b+c}=\)

\(\cfrac{x^3+y^3+z^3-3xyz}{ax+by+cz}\)





বা, \(\cfrac{(x^2+y^2+z^2-xy-yz-zx)}{(a+b+c)}=\)

\(\cfrac{(x+y+z)(x^2+y^2+z^2-xy-yz-zx)}{(ax+by+cz)}\)




বা, \(\cfrac{1}{(a+b+c)}=\cfrac{(x+y+z)}{(ax+by+cz)}\)
বা, \((a+b+c)(x+y+z)\) \(=ax+by+cz\)

(প্রমাণিত)


Similar Questions